2020
DOI: 10.1016/j.breast.2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Health state utilities for metastatic breast cancer in Taiwan

Abstract: Background New developments in medications for metastatic breast cancer (MBC) can be of great benefit to patients, but unfortunately these medicines also increase expenditures. Cost-utility analyses (CUAs) are needed to allocate health resources properly, and health utility values are required to calculate quality-adjusted life years in those CUAs. Objective The aims of this study were to measure health utility values for several MBC-related health states and certain br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The transition probabilities for each Markov state in our model were calculated based on the EMILIA trial using the DEALE method, with the equation of P = 1‐(0.5) (1/median time to event) 2,3 (Table 1). Health state utilities were derived from a study previously conducted in Taiwan 4 . Only direct medical costs were considered in our study.…”
Section: Subject Base‐case Value Distributionsmentioning
confidence: 99%
“…The transition probabilities for each Markov state in our model were calculated based on the EMILIA trial using the DEALE method, with the equation of P = 1‐(0.5) (1/median time to event) 2,3 (Table 1). Health state utilities were derived from a study previously conducted in Taiwan 4 . Only direct medical costs were considered in our study.…”
Section: Subject Base‐case Value Distributionsmentioning
confidence: 99%
“…The range of variability they report for these HSUVs is comparable to the fixed error found in our study. Tachi et al 15 and Chou et al 23 also reported that adverse events during chemotherapy were associated with lower HSUVs, as did Lloyd et al 9 Second, the guidelines for conducting cost-effectiveness analyses in Japan’s healthcare sector recommend that sensitivity analysis be conducted. Cost-effectiveness analysis involves uncertainty in the analytical framework and the data itself.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, based on published research and China's GDP (gross domestic product), the WTP thresholds were determined to be $150,000/QALY and $37,653/QALY (3 times China's GDP per capita in 2021) to evaluate the cost-effectiveness of the US and China [ 22 , 23 ]. Since no health utility was reported in clinical trials, the average health utility for PFS and PD status was assumed to be 0.70 and 0.50, respectively, using previously published articles [ 20 , 24 , 25 ]. We also corrected for mean health utility by disutility due to grade 3/4 AEs [ 20 , 22 , 26 , 27 ]( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%